Caracterização geo-ecológica dos sistemas de cordões dunares da Estremadura - Henriques, Maria Vergínia; Neto, Carlos (Finisterra, 2002)
GEO-ECOLOGYCAL STUDY OF SOME DUNE SYSTEMS IN THE PORTUGUESEESTREMADURA. The Portuguese Estremadura coastal area between Nazaré and Peniche displays great variety of landforms. Most are cliff systems cut in sedimentary rocks with incisions controlled by tectonic activity. In the river mouths sand bars and beaches are present. Beach systems make up about 40% of the referred coastline and have ridges of diverse form and size, and rates of vegetation cover. These dunes appear on the inland side of the beach or even backshore as a result of erosion. They may have piled up into sand backs that cut off the lagoon estuaries to the West in the historic period. The geomorphologic and sedimentary characteristics that appear permit the identification of double ridges separated by interdunal corridors or depressions in West Nazaré, S. Martinho do Porto and Peniche (Consolação) and in a simple and continuous form in Baleal. This difference could be related with local topography, wind/wave climatology and/or vegetation cover. With regard to flora and vegetation, psammphitic and halonitrophilous pioneer plants that colonise foreshore ecosystems and transitions to backshore are Salsolo kali-Cakiletum aegyptiacae in the studied area. Springtime terophitic is sparse and grows where organic remains have accumulated. Flat backshore areas which are overrun by sea during spring-tides and storms are colonised by open vegetation, predominantly Elymus boreli-atlanticus (Euphorbio-Agropyretum junceiformis). Alongside the clumps of marran grass, on the backshore and on the crests of white dunes, Loto-Ammophiletum grows abundantly together with Otanthus maritimus and Lotus creticus. Grey dunes, which are further away from the effects of the ocean (winds and salinity), are characterised by relative sand stability and a succession of dune peaks and interdune corridors with thermophilic associated Armerio welwitschii-Cruciannelletum. The openings display terophitic associated Violo-Silenetum litoreae with Atlantic features. The mature stage of the system consist in the more interior stabilised dune of dense shrubs, consisting mostly of Juniperus turbinata (Osyrio-Juniperetum turbinatae).